The mid-mesial canal prevalence in mandibular molars of a Saudi population: A cone-beam computed tomography study - Mazen A. Aldosimani; Riyadh I. Althumairy; Adel Alzahrani; Fahd A. Aljarbou; Mohammed S. Alkatheeri; Muhannad A. AlGhizzi; Turki K. Abughosh (Saudi Dental Journal)
Introduction: The aim was to assess the prevalence of Mid Mesial Canal (MMC) in the first and second mandibular molars in a Saudi subpopulation sample and assess its relation to side, gender, and age using Cone beam computed tomography (CBCT). Methods: The CBCT scans at King Saud University Dental Hospital between 2016 and 2019 were reviewed and filtered. The MMC of the mandibular molars were assessed according to Pomeranz et al. classification which was: (1) independent; (2) fin; (3) confluent with the mesiobuccal canal; and (4) confluent with the mesiolingual canal. Three calibrated observers examined the MMC on all planes at both sides. Age and gender factors were used to analyze that prevalence. A chi-squared test was used and (P ≤ 0.05) was considered to be statistically significant. Results: 395 patients, and 1377 teeth met the inclusion criteria. The total number of mid-mesial canals was 12 (0.9%): nine at the mandibular first molar (1.3%) and three in the mandibular second molar (0.4%). The most common type of mid-mesial canal was confluent (n = 10), of which 6 fused with the mesiobuccal canal and 4 fused with the mesiolingual canal. Two canals were of the fin type, and there was no instance of independent mid-mesial canal. There was no significant difference between all variables: tooth type, tooth side, patient gender, and patient age group (p > 0.05). Conclusion: In this study, the most common MMC configuration was the confluent type followed by the fin type and no independent type were found. The patient side, gender and age did not influence the prevalence of the MMC.